An Exploration of Students’ Difficulties in Using Critical Thinking Skills in Reading - Velayati, Nidar; Muslem, Asnawi; Fitriani, Siti Sarah; Samad, Iskandar Abdul (Institut Agama Islam Negeri Imam Bonjol Padang, 2017)
This study intends to explore students’ difficulties in using critical thinking skills in reading. The subject of this study was second year undergraduate students of Ar-Raniry State Islamic University, Banda Aceh. This qualitative study analysed students’ difficulties in using critical thinking skills in term of interpretation, analysis, evaluation, inference, explanation, and self-regulation. A personal interview was conducted to find the data from the students. The result indicates that students’ lack of practicing let them difficult in using critical thinking skills in reading. The other difficulties found were lack of language mastery, implied meaning, background knowledge, repetition and lack of vocabulary. Among six problems discovered above, lack of practicing, background knowledge and language mastery had made the students felt that critical thinking was difficult to be applied.